Avaliação de risco ecológico de pesticidas para organismos aquáticos em três microbacias da Bacia Hidrográfica do Rio São Lourenço-MT - Silva, Kennefer Leite (2023)
Mato Grosso is the main consumer of pesticides and the greatest power in agricultural production in the country, with soy, corn and cotton asthe main crops planted. The intensive use of these substances in crops can cause the presence of residues that eventually can reach toxic levels for living organisms. Therefore, the objective of this work was to evaluate the risk to the aquatic environment in surface waters of three microbasins, in the São Lourenço River Basin, located in the municipalities of Campo Verde, Jaciara and Rondonópolis based on secondary data obtained from monitoring. The risk assessment was based on pre-registration (ecotoxicity tests) and post-registration (environmental concentrations). The concentrations and detection frequencies of pesticides were used to determine the exposure of aquatic organisms, followed by comparison with ecotoxicological parameters for three trophic levels: algae, aquatic invertebrates and fish, from which the Risk Quotient was calculated as recommended by the Commission European. Monitoring data were obtained using punctual and passive sampling techniques. Punctual sampling allowed the detection of 18 pesticides, while passive sampling showed the highest number of pesticides detected (24), but in lower concentrations. The most detected pesticides were atrazine, metolachlor, carbofuran, malathion, carbendazim and cyproconazole. Pesticides detected in higher concentrations were carbendazim (6,0 µg L⁻¹), malathion (0.59 µg L⁻¹), carbofuran (0.56 µg L⁻¹) and atrazine (1.3 µg L⁻¹). In the ecological risk assessment, RQ >1 was found for seven pesticides when considering extreme concentrations with low frequency, due to nonpersistent punctual events, therefore, there is no indication of long-term effects. Analyzing the physical and ecotoxicological properties of the pesticides, it was not possible to affirm the existence of risk for 5 pesticides (carbendazim, ethyl chlorimuron, carbofuran, pyraclostrobin and teflubenzuron) that presented RQ >1, however it was observed that chlorpyrifos and malathion presented a potential risk for the aquatic organisms in the three study regions, although also with low frequency.